The feelings of singing and its importance and interpretation in the opera lyric of the belcanto - Zelenkova, Dagmar (Aura musica, 2012)
The declaration of feelings and sentiments and the base of the opera lyric and the theory of the feelings help to understand the inspiration of the music of belcanto. The singer has to prefer the good technique of the singing, which is the only way to understand deeply the interpretation of the feelings. Only that way one can talk about the credible expression of the canto.
Keywords: theory of the feelings; belcanto; technique of the singing; expression of the canto